2014
DOI: 10.1093/her/cyu039
|View full text |Cite
|
Sign up to set email alerts
|

The differentiated effectiveness of a printed versus a Web-based tailored physical activity intervention among adults aged over 50

Abstract: This study provides insight in the effectiveness of a print-delivered and a Web-based physical activity (PA) intervention (with or without additional environmental information on local PA possibilities) among people aged over 50. Intervention groups (print-delivered basic [PB; n = 439], print-delivered environmental [PE; n = 435], Web-based basic [WB; n = 423], Web-based environmental [WE; n = 432]) and a control group (n = 411) were studied in a clustered randomized controlled trial. Participants received thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 47 publications
0
68
1
3
Order By: Relevance
“…Although SDT postulates that all humans have the same basic psychological needs, previous studies on tailored PA interventions have shown that participant characteristics such as age, gender, BMI, intention to be physically active at baseline and PA at baseline can influence the effects of tailored PA interventions (Peels et al, , 2014Spittaels & De Bourdeaudhuij, 2007;Van 't Riet, Crutzen, & De Vries, 2010;van Stralen, de Vries, Bolman, Mudde, & Lechner, 2010). This is relevant in the context of our study, since the impact of both our interventions might be more pronounced in subgroups of participants with specific characteristics.…”
Section: Self-determination Theory and Motivational Interviewingmentioning
confidence: 85%
See 2 more Smart Citations
“…Although SDT postulates that all humans have the same basic psychological needs, previous studies on tailored PA interventions have shown that participant characteristics such as age, gender, BMI, intention to be physically active at baseline and PA at baseline can influence the effects of tailored PA interventions (Peels et al, , 2014Spittaels & De Bourdeaudhuij, 2007;Van 't Riet, Crutzen, & De Vries, 2010;van Stralen, de Vries, Bolman, Mudde, & Lechner, 2010). This is relevant in the context of our study, since the impact of both our interventions might be more pronounced in subgroups of participants with specific characteristics.…”
Section: Self-determination Theory and Motivational Interviewingmentioning
confidence: 85%
“…Therefore, the present study also aimed to identify participant characteristics that modify the intervention effects, by conducting moderator analyses. These analyses will include variables that moderated the effects of tailored interventions in earlier studies such as age, gender, BMI, intention to be physically active at baseline and PA at baseline (Peels et al, , 2014Spittaels & De Bourdeaudhuij, 2007;Van 't Riet et al, 2010;van Stralen et al, 2010). The moderator analyses will identify in which participant subgroups the SDT/MI-based and the traditional intervention exert the greatest effects, enabling a more in-depth view on the impact of both interventions.…”
Section: Self-determination Theory and Motivational Interviewingmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of shortening the intervention content by tailoring the use of components to user’s preference,10 it may have been more effective to offer participants only components adapted to their level of motivation to change their behavior; Stanczyk et al55 found this strategy effective. Peels et al56 tested a web-based basic version of their program and a version in which they added additional environmental information with links to other resources to increase physical activity in adults aged 50 and over. They found that only the latter was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…Age was categorised into (<55y and ≥55y). Although the standard cut off used to define 'older adults' is 65 years, the ≥55y group is a useful target for physical activity interventions to help them to establish healthy physical activity habits and reduce their risk of disease before they enter into the 65+ age group [35]. People over 55y have lower Internet literacy than younger age groups and it is therefore likely that they will interact and engage with Web 1.0 and Web 2.0 features differently to younger adults [25].…”
Section: Measures Demographicsmentioning
confidence: 99%